Penerapan Nilai Pendidikan Konservatif Pada Anak Usia Dini - Mizna Laila Albaar; Radjiman Ismail; Natsir Machmud (Jurnal Ilmiah Wahana Pendidikan, 2023)
Islamic education (Al Tarbiyah Al Islamiyah) is an effort to prepare humans to live perfectly and happily, love the motherland, perfect manners, orderly thoughts, refined feelings, proficient at work, sweet speech both orally and in writing.In this study, researchers used library research. Conservatism is a political philosophy that supports traditional values.Conservatism education is an ancient Islamic education that maintains educational ideology in style and variety, so that it can keep abreast of the times even though it is sometimes late in its application. Conservatism is a political philosophy that supports traditional values.